Produção de mudas de espécies florestais inoculadas em dois tipos de recipientes - Andraus, Michel de Paula (2017)
Nowadays there is an increasing environmental pressure, which causes industries to develop new alternatives for the destination of residues generated by industrial processes. The costs of construction and maintenance of industrial landfills and the environmental risks that are involved in this process have aroused the interest of several industries in studying the feasibility of residues application in agriculture. One of the alternatives for agroindustrial residues is the substrate for seedlings. In view of the above, it is verified that the use of containers of agroindustrial residues pressed together with the inoculation of rhizobia and mycorrhizal fungi can bring numerous benefits to the production of forest seedlings and also to the environment. However, the association of these practices has not been sufficiently studied. The objective of this work was to evaluate the phytotechnical aspects of three forest species when cultivated in pressed blocks, composed of different proportions of agroindustrial residues and convenctional plastic tubes, and the effect of inoculation with rhizobia and mycorrhizal fungi on these seedlings. For that, an experiment was carried out in which four compounds with different ratios of sugarcane bagasse, filter cake, coconut fiber and aviary waste were made. In the pressed blocks of the selected composted substrate were planted seeds of Acacia manigium, Sesbania virgata and Eucalyptus grandis. The first two species were inoculated with rhizobia and mycorrhizal fungi specific for each species, and eucalyptus only with mycorrhizal fungi. At 70 days after sowing, mycorrhizal colonization, nodulation, phytotechnical and nutritional parameters were evaluated. And the data were submitted to analysis of variance and test of comparison of means. It was verified that the pressed blocks of agroindustrial residues do not provide better development of seedlings of Acacia mangium and Eucalyptus grandis in relation to the conventional tube. Inoculation with rhizobia, alone or associated with arbuscular mycorrhizal fungi in the seedling production phase, provides better development of the Acacia mangium species. The seedlings of Sesbânia presented better development with the system of production of seedlings in pressed blocks, made with agroindustrial residues. It could be observed that the response to the use of the pressed blocks depends on the species that will be used.